Penilaian Masyarakat terhadap Kondisi Eksisting Pasar Tradisional yang Dikelola oleh Pemerintah Kota Padang - Yosi Suryani; Rudy Rinaldy (Politeknik Negeri Padang, 2019)
This study aims to analyze eight traditional markets managed by the Padang City Government. This analysis is to provide recommendations for changes or improvements to each traditional market which is one of the drivers of the economy of community, especially Padang City. The method of data collection is carried out on two types of data, namely primary data and secondary data. Primary data through structured interviews in the form of questionnaires given to each buyer who visited eight traditional markets managed by the Padang City Government. While secondary data is obtained from agencies or agencies that are related to the object of research. The indicators used are hygiene factors, accessibility factors, merchant and goods factors, supporting support factors and supporting infrastructure factors. The results of the analysis conclude that from the eight traditional markets managed by Padang City Government, Bandar Buat Market, Tanah Kongsi Market, Alai Market and Market Siteba ranks Very Good. While the Simpang Haru Market, Ulak Karang Market and Lubuk Buaya Market have a Good rating, and the Belimbing Market has a Pretty Good rating. With these results, it is recommended to recommend a number of traditional markets that must be arranged, and developed, namely: Bandar Buat Market, Haru Simpang Tanah Kong, Ulak Karang, Alai, Siteba, Belimbing, and Lubuk Buaya, although the facilities are complete and the results of the buyer's assessment are good. Drainage repair, arrangement of parking locations, availability of clean water are things that must be considered to create security and comfort for buyers and sellers.